Differentiated Thyroid Cancer in Navarra (Spain): Historic Cohort Results (1987–2003). (31st July 2011) - Salvador Egea, María Pilar; Echegoyen Silanes, Ana Aranzazu; Layana Echezuri, Eduardo; Anda Apiñariz, Emma; Puras Gil, Ana; Menéndez Torre, Edelmiro; Forga Llenas, Lluis; Sainz de los Terreros, Amaya
Abstract : Introduction . Navarra has the highest incidence of differentiated thyroid cancer in Spain. The aim of this study was to review its management carried out by the Navarra's multidisciplinary Thyroid Disease Unit, from 1987 to 2003. Material and Methods . 325 patients were studied to find the incidence, prevalence, and prognostic factors. Statistical analysis comprised univariate and multivariate Cox proportional hazards regression models for survival and tumor recurrence. Results . The average annual incidence was 3.6 per 100, 000 inhabitants, with a final prevalence of 82.4 per 100, 000. Regarding survival and recurrence, statistical significance was observed for stage IV, follicular carcinoma, capsular and prethyroid muscles invasion, and T4 group. Only survival was related to tumour size larger than 40 mm. Only recurrence was related to lymph node metastases and radioiodine dose higher than 100 mCi. Conclusions . Attendance of patients in a functional unit setting has allowed us to classify them into three risk groups.